EFL Learning Improvement Through the SAMR Learning Model: A Technology Integration Framework in the Digital Era - Siti Wahdatul Alawiah; Yayu Heryatun; Fadilla Oktaviana; Purnama Rika Perdana (Jurnal Impresi Indonesia, 2026)
The rapid development of digital technology has transformed the landscape of English as a Foreign Language (EFL) education, making technology integration not only beneficial but essential. This study examines the application of the SAMR (Substitution, Augmentation, Modification, Redefinition) model as a framework for enhancing learning outcomes in digital EFL environments. Through a literature review approach, the research synthesizes findings from recent studies to identify effective strategies, pedagogical benefits, and challenges associated with implementing technology using the SAMR model. The analysis indicates that technology integration at the higher levels of SAMR—Modification and Redefinition—enables deeper learning experiences by promoting collaboration, creativity, and communicative competence. Meanwhile, even basic levels of integration, such as Substitution and Augmentation, contribute to improved efficiency and accessibility of EFL learning materials. However, the study also highlights challenges, including limited digital literacy among teachers, inadequate infrastructure, and varying student readiness. Overall, the findings demonstrate that the SAMR model plays a significant role in enhancing student engagement, interactivity, and autonomy, ultimately supporting more meaningful and dynamic EFL learning in the digital era.